Determination of Copper and Lead in Samples of Fungicides and Insecticides in Diyala Governorate - Zeina Gany Fadeel1, Suaad k.Abd-Alwahab1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This investigation included the estimation of heavy metals (copper, Cu and lead, Pb) in four types of pesticides that were been selected randomly from commercial markets in the Governorate of Diyala. Two types of insecticides (Lambada Cyhalothrin 5% EC and Zoro Super) and two types of fungicides (Folicur and Goldtanol 50% SL) were tested. The results showed that the highest concentration of lead was found in the insecticide Lambada Cyhalothrin 5% EC (5.621 Mg. l?¹), while the lowest value was recorded in the fungicide Folicur (0.147 Mg. l?¹). The highest concentration recorded for copper was found in the fungicide Goldtanol 50% SL (28.323 Mg. l?¹) whereas a much lower value was found in the pesticide Lambada Cyhalothrin 5% EC (5.995 Mg. l?¹). When a search of pesticides banned in the Gulf Cooperation Council (GCC) was performed it was found that the insecticide Lambada Cyhalothrin 5% EC is among the banned pesticides.